2020
DOI: 10.3390/f11101046
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Tree Health under Increasing Climate and Trade Challenges: Social System Considerations

Abstract: Tree and forest health is increasingly influenced by climate change as well as growing globalisation and trade. Climate change enables species to colonise new environments, and species that previously were constrained by native predators are now able to flourish in these new environments with little or no resistance. Additionally, the growing trade in live plants and wood products results in the inadvertent movement of species (such as pests or fungi in soil) from far away areas of the globe. As a result, new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, forests worldwide are facing many increasing anthropogenic pressures. Climate change is altering their environmental conditions, while human travel and trade is assisting the spread of tree pests and diseases outside their natural ranges [1][2][3][4][5]. Global warming is likely to increase the negative impacts of pests and diseases [6], which can cause global and local declines and extinctions of valuable tree species.…”
Section: Introduction 1global Threats Require Holistic Responsesmentioning
confidence: 99%
“…However, forests worldwide are facing many increasing anthropogenic pressures. Climate change is altering their environmental conditions, while human travel and trade is assisting the spread of tree pests and diseases outside their natural ranges [1][2][3][4][5]. Global warming is likely to increase the negative impacts of pests and diseases [6], which can cause global and local declines and extinctions of valuable tree species.…”
Section: Introduction 1global Threats Require Holistic Responsesmentioning
confidence: 99%
“…China's forest products industry has gradually emerged from its large-but-weak position and begun to mature and participate more competitively in global value chains. As a result of low-cost manufacturing and the surge in foreign demand, China has become a center for the remanufacturing and redistribution of wooden products [1][2][3]. However, the studies of Moinul et al (2016) have shown that imports and exports of wooden forest products can result in pollution, and the environmental impacts of trade in wooden products have aroused great concern [4].…”
Section: Introductionmentioning
confidence: 99%